Hermeneutic Phenomenological Study of Nepalese Migrant Worker’s Families from Communication Perspective - Acharya, Trishna (Journal of Janta Multiple Campus, 2024)
This research study is conducted to explore the role of intrapersonal communication on human development of international migrant workers' left behind family (IMWLF). It considers these left behind families to have difficult life conditions due to the separation with their family members. It includes the experience of migrant workers' left behind son, daughter and spouses. Study has explored the variation in qualitative experience in this life condition due to their gender identity. Major focus is on human physiological, psychological, emotional, cognitive, intellectual and spiritual development. Hermeneutic phenomenological qualitative study is conducted through an in-depth interview of 4 participants from international migrant workers' left behind families based on interpretive research philosophy in a cross-sectional time frame on inductive approach. Inductive approach is implied to see the individual development within a wider area of human development. Major finding of this study is that family separation caused by migrant working has highly impacted their human development in various spheres as in studied variables such as physiological, psychological, emotional, cognitive, intellectual and spiritual level. Positive intrapersonal communication skills enhancement is explored as needed for intervention for the qualitative human development of these research participants in specific and in general of international migrant workers left behind families in Nepal.